The impacts of human resource development (HRD) practices on utm academic staff’s job satisfaction - Sia, Shi Xuan (2013)
This study investigates the impact Human Resource Development practices on UTM academic staff’s job satisfaction. There are four elements of HRD will be investigated which are i) Training and development, ii) Organization development, iii) Career development, and iv) Performance management. The research was conducted in Universiti Teknologi Malaysia (UTM), Skudai branch, Johor Bahru, and the respondents in this study were academic staff. A total of 95 questionnaires collected out of 1110 questionnaires distributed, indicating 8.5 percent rate of return. The methods applied in this study include Chi Square test, Mean score analysis, Spearman Rho’s correlation analysis, simple linear regression analysis, and multiple regression analysis. There are four main results in this study. First, the Chi Square test showed that there is no significant difference among demographic factors on academic staff’s job satisfaction. Second, mean score analysis showed that the highest satisfaction level among variables was career development, follow by overall job satisfaction, organization development, training and development, and performance management. Third, Spearman Rho’s correlation analysis revealed that there is significant association between HRD practices with job satisfaction. Interesting, the regression result showed that HRD practices has positive significant effect on academic staff’s job satisfaction. Lastly, regression result showed that career development was found to be the most influential on academic staff’s job satisfaction, and then follow by organization development, performance management, and training and development.